2013
DOI: 10.1016/j.apergo.2012.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Ground reaction forces and plantar pressure distribution during occasional loaded gait

Abstract: A B S T R A C TThis study compared the ground reaction forces (GRF) and plantar pressures between unloaded and occasional loaded gait. The GRF and plantar pressures of 60 participants were recorded during unloaded gait and occasional loaded gait (wearing a backpack that raised their body mass index to 30); this load criterion was adopted because is considered potentially harmful in permanent loaded gait (obese people). The results indicate an overall increase (absolute values) of GRF and plantar pressures duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 44 publications
7
67
0
Order By: Relevance
“…For the in-shoe plantar pressure data treatment, first the program divided the foot into 10 regions: hallux, distal phalanges, medial, central, and lateral forefoot, medial and lateral midfoot, and medial, central, and lateral rearfoot, as used in another study (Castro et al, 2013). The program automatically divided the foot, and the regions were checked by two trained researchers, who, if necessary, manually corrected this procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the in-shoe plantar pressure data treatment, first the program divided the foot into 10 regions: hallux, distal phalanges, medial, central, and lateral forefoot, medial and lateral midfoot, and medial, central, and lateral rearfoot, as used in another study (Castro et al, 2013). The program automatically divided the foot, and the regions were checked by two trained researchers, who, if necessary, manually corrected this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The program calculated the plantar pressure peaks, which were considered the highest pressure sensor value during the third step, and their time of occurrence for each region. We used the vertical GRF to calibrate the plantar pressure data trial by trial, as suggested by Castro et al (2013). All data (GRF and pressure peaks) were showed as absolute and normalized (scaled to BW) values.…”
Section: Discussionmentioning
confidence: 99%
“…However, technology has significantly improved since that time, and sensor resolution and software specifications are today able to investigate changes to those plantar pressure areas, which inevitably had to be previously disregarded. Although foot masking in 10 different plantar areas has been previously carried out [21][22][23], this research demonstrates for the first time that both PP and PTI provided repeatable and reproducible data in all 10 masked areas of the foot when using the F-Scan system in children.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the in-shoe pressure system data, the program automatically divided the footprint into 10 plantar foot regions, as previously proposed (3) : hallux, distal phalanges, medial, central and lateral forefoot; medial and lateral midfoot; and medial, central and lateral rearfoot. One of the researchers verified this procedure and, eventually, the boundaries between the foot regions were manually corrected.…”
Section: Discussionmentioning
confidence: 99%
“…For each of the 10 plantar foot regions the program calculated one outcome measure: the plantar pressure peak, which was considered the highest pressure value shown on the sensor during the stance phase when the participant stepped on the force plate. We used the force plate to calibrate the plantar pressure data as previously proposed (3) .…”
Section: Discussionmentioning
confidence: 99%